Hegel's concept of action - Quante, Michael 1962- (Modern European philosophy, 2004)
This book is an important gateway through which professional analytic philosophers and their students can come to understand the significance of Hegel's philosophy for contemporary theory of action. As such it will contribute to the erosion of the sterile barrier between the continental and analytic approaches to philosophy. Michael Quante focuses on what Hegel has to say about such central concepts as action, person and will, and then brings these views to bear on contemporary debates in analytic philosophy. Crisply written, this book will thus address the common set of preoccupations of analytic philosophers of mind and action, and Hegel specialists